"Essays in Medieval Studies". Proceedings of the Illinois Medieval Association <http://www.luc.edu/publications/medieval/>, 2001 - Simone Bordini (Reti Medievali Rivista, 2002)
Recensione a "Essays in Medieval Studies". Proceedings of the Illinois Medieval Association <http://www.luc.edu/publications/medieval/>, 2001